Nanomechanical Gas Sensing with Laser Treated 2D Nanomaterials. Issue 12 (3rd November 2020) - Mistry, Kissan; Ibrahim, Khaled H.; Novodchuk, Inna; Ngo, Hyunh Thien; Imamura, Gaku; Sanderson, Joseph; Yavuz, Mustafa; Yoshikawa, Genki; Musselman, Kevin P.
Abstract: 2D nanomaterials such as graphene oxide (GO), molybdenum disulfide (MoS2 ), and tungsten disulfide (WS2 ) are viable candidates for use in chemical gas sensors due to their large specific surface area available for analyte adsorption. In this work, these 2D materials are treated with a femtosecond laser process to intentionally introduce defects, dopants, and functional groups to the material for improved gas adsorption properties. The materials are coated onto a nanomechanical membrane‐type surface stress sensor (MSS) to evaluate their sensing capability toward a select group of volatile organic compounds. By utilizing the MSS platform, the approach avoids the need for 2D materials with conductive properties typically required in chemoresistive sensors. The results show that a longer laser treatment time for graphene oxide increases the sensor response, which is attributed to an increase in defects and oxygen functional groups. Doping of graphene oxide with boron nitride improves sensor response, likely due to the introduction of pyrrolic nitrogen groups with high chemical activity. Additionally, the graphene oxides demonstrate partial selectivity toward the detection of toluene, attributable to π–π interactions. MoS2 and WS2 nanoflakes also show enhanced sensor response attributed to the formation of apical/bridging sulfur bonds with high catalytic activity. Abstract : 2D nanomaterials such as graphene oxide, molybdenum disulfide, and tungsten disulfide are treated with a femtosecond laser to introduce defects, dopants, and functional groups for improved gas sensing capability. The materials are coated onto nanomechanical membrane‐type surface stress sensors for the detection of volatile organic compounds.